A Model of Homogeneous Input Demand Under Price Uncertainty - Wolak, Frank A.; Kolstad, Charles D. (American Economic Review, 1991)
This paper examines the empirical validity of a model of homogeneous input demand under price uncertainty in which firms trade off expected input cost against its variability (risk) in selecting the optimal input supplier mix. Using recent work in time-series econometrics, this model is applied to the Japanese steam-coal import market, where five suppliers compete: China, the Soviet Union, South Africa, the United States, and Australia.